Price System and Subsidies in Peruvian Agriculture: 1985-1987 - Escobal, Javier A. (1987)
The spectacular initial success of the Aprista Administration's macroeconomic and agrarian policies, as well as the predictability of its subsequent failures are phenomena worthy of analysis. This article analyzes the evolution of agricultural price and subsidy policies implemented in Peru since July 1985. Estimates of direct price subsidies for agricultural inputs and outputs, credit subsidies, awarded by the Agrarian Bank, and exchange rate subsidies have been carried out. The article also reviews the main effects of these policies on income distribution. The author concludes that the agrarian reactivation program put forward by the Aprista Administration began to collapse in 1987, mainly because of the negative efects of its system of highly differentiated and overvalues exchange rates.